Trade: The free flow of goods and food security and nutrition - Martin, Will; Laborde Debucquet, David (International Food Policy Research Institute, 2018)
The benefits of international trade are embedded in our everyday lives, our meals have been shaped by globalization, and many farmers profit from export markets for their products. Global improvements in food and nutrition security under an open and inclusive trade regime have contributed to falling levels of undernourishment, better nutrition and greater dietary diversity, and overall economic development. Trade contributes to the four key requirements of food security—food availability, access, utilization, and stability of supply. Over the last 40 years, the share of food, measured in calories, crossing an international border rose from 12.3 percent to over 19 percent. But in today’s climate of skepticism about globalization, with longstanding trade agreements such as the North American Free Trade Agreement (NAFTA) under threat, the benefits of trade may be forgotten as negative impacts are emphasized by advocates of trade barriers and self-sufficiency. In this paper, we examine the links between trade and food security, drawing on evidence from history and economics and from the available data.